Studies on the explosion protection in hazardous area based on intrinsically safe method exi according to iec60079-14 - Cham, Leslie Yeong Lie (2022)
Explosion protection is indispensable in the industry operating in an atmosphere filled with combustible substances. Intrinsic safety (Ex i) is one of the explosion protection methods which can restrict the energy entering the hazardous area and limit the energy reserved in the field devices. Furthermore, it is mostly applied in the control and instrumentation system. The project aims to examine the conformity of various Ex i systems as per IEC 60079-14. The objectives are to verify the compliance of the apparatuses and carry out the analysis on the intrinsic safety loop verification. Additionally, the emphasis is put on the verification regarding the validity of the Ex i systems that implement temperature sensing and the controlling of the solenoid valve. Throughout the project, the experiment and site visit are not implemented. The specifications of the apparatuses and the configuration of the Ex i systems are obtained from the datasheets of the companies specializing in explosion protection such as Eaton MTL, Pepperl+Fuchs and Phoenix Contact. Based on the parameters and certification of conformity shown in the datasheets, the compliance of apparatuses and intrinsic safety loop can be examined. In this project, the conformity of four Ex i systems has been validated in terms of the compliance of the apparatuses and the intrinsic safety loop verification. The ways to implement the validation regarding the compliances of various apparatuses including temperature transducer, digital display, temperature sensors, solenoid valves and intrinsic safety barriers have been demonstrated. Furthermore, the proper way to utilize the energy curves in the verification of the safety parameters is covered. Apart from that, the intrinsic safety loop verification of several Ex i system configurations is executed. In addition, the flowcharts and equations are presented to interpret the intrinsic safety loop verification more understandably. In short, the conformity of all of the four Ex i systems is proven and the detailed steps of the verification are shown, thus providing clearer guidelines on the implementation of Ex i method as per IEC 60079-14.